Chinese herb-crosslinked polysaccharide hydrogel loading DFO accelerates diabetes wound healing - Li, Ruping; Wu, Yanxin; He, Lvchen; Yang, Ruotong; Luo, Kaipei; Gao, Fei; Yuan, Haipo; Zheng, Yu; He, Yao (Materials & design, 2025)
[Display omitted] •Diabetic wounds are closely related to inflammation, impaired angiogenesis and bacterial infection, so it is urgent to develop hydrogel with antibacterial, anti-inflammatory, and proangiogenic functions.•Carboxymethyl chitosan (CMCS) has excellent biocompatibility and fast gel properties, deferoxamine (DFO) can promote angiogenesis, and luteolin (LUT) has unique advantages in diabetic wound treatment.•The DFO and LUT complex polysaccharide hydrogel prepared in this study had antibacterial and antioxidant properties, promoted cell migration, enhanced angiogenesis through HIF-1α and VEGFA pathways.•C/DFL hydrogel has sustained release, high permeability and good biocompatibility, which can be used as an ideal antimicrobial dressing for diabetic wounds, significantly promoting wound healing. The wound of diabetes is closely related to inflammation, reactive oxygen species production, impaired angiogenesis and bacterial infection. It is urgent to develop a hydrogel dressing with antibacterial and anti-inflammatory properties and promoting angiogenesis to achieve efficient wound healing. Carboxymethyl chitosan (CMCS) is obtained by chemical modification of chitosan, which has excellent biocompatibility and rapid gel properties. Deferiptyline (DFO) has the ability to increase the expression of HIF-1α, which promotes the release of endogenous growth factors related to angiogenesis. Luteolin (LUT), the active ingredient of traditional Chinese medicine, shows unique advantages in treating diabetes wounds. In this study, polysaccharide hydrogel prepared by combining DFO and LUT has excellent antibacterial and antioxidant properties, promotes cell migration, releases LUT and DFO at the wound site, and enhances angiogenesis through HIF-1α and VEGFA pathways. The hydrogel synergistically promotes cell migration, angiogenesis and effectively eliminates drug-resistant bacteria, which is beneficial to wound healing of diabetes. This study has created a multifunctional hydrogel loaded with DFO and crosslinked polysaccharide, an active ingredient of traditional Chinese medicine, with sustained release, enhanced permeability and great biocompatibility, which can be used as an excellent antibacterial dressing for diabetes wounds.